QUALITY OF POPULATION ADMINISTRATION OF HEIRS' LETTERS THROUGH THE SUPERLARIS IN TULANGAN VILLAGE, TULANGAN DISTRICT, SIDOARJO REGENCY - Setianingrum, Syaharani; Choiriyah, Ilmi Usrotin (Proceeding of International Conference on Social Science and Humanity, 2025)
Objective: The purpose of this study is to analyze the factors that contribute to or hinder efforts to improve the quality of public services, especially in the service of issuing heirs' letters through the Si Superlaris program at the Tulangan Village Office, Tulangan District, Sidoarjo Regency. Improving service quality is closely related to human resource development and the application of service quality dimensions. Methods: This study uses a qualitative descriptive approach, and the five main dimensions are physical evidence, reliability, responsiveness, assurance, and empathy. Data is collected through thorough interviews, observations, and documentation with key informants such as implementing devices. Results: The results of the study show that these five dimensions have a positive impact on service quality, although there are obstacles in the form of limited human resources, time constraints, and lack of public awareness in preparing required documents. These obstacles do not reduce the effectiveness of the Si Superlaris program which is able to increase service efficiency and public trust. Novelty: The novelty of this research lies in the analysis of the implementation of the Si Superlaris program at the village level as a website-based heir's letter administration service. The integration of the SERVQUAL dimension in the context of village government shows that the principle of service quality can be applied effectively to local administrative services and become a model for other community service innovations.